Case Analysis on Economic Efficiency of Grid-Connected Photovoltaic Power Generation Project with Carbon Emission Measurement. (June 2018) - Peng, Peng; Gao, Yubo; Yu, Guoqin; Lou, Xiaodong; Dai, Yaping; Chen, Zhonghu
Abstract: Taking the photovoltaic power generation project in Shanghai area as a case, economic benefit of the whole lifetime cycle of the project was analyzed by adopting the levelized cost of electricity (LCOE). Meantime in consideration of the low-carbon economic benefits, the incremental cost analysis method was applied to evaluate the unit carbon-mitigation cost of the project and sensitivity analysis was conducted, in ordering to put forward the guiding suggestions for the investment of photovoltaic power generation projects.